Implementation of Cooperative Mobile Application Design using the Design Thinking Method - Johan Prasetyo; Istian Kriya Almanfaluti; Andry Rachmadany (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to design a digital cooperative application prototype using the Design Thinking method and evaluate its usability using the Single Ease Question method. The research employed a descriptive quantitative approach consisting of empathize, define, ideate, prototype, and test stages. Data were collected through interviews, observations, and questionnaires distributed to cooperative members. The findings revealed several problems, including slow administrative processes, lack of data transparency, and the absence of payment reminder systems. Based on these findings, a prototype application was developed featuring login, digital payment, financial reports, loan applications, and profile management. Testing involved 100 respondents using the SEQ method and produced an average score of 6.4 out of 7. The results indicate that the application is categorized as easy to very easy to use. Therefore, the Design Thinking method effectively produced a user-friendly digital cooperative application prototype that meets user needs.